Art beyond context: a sociological inquiry into the singularity of cultural creativity - Silva,Augusto Santos (2021)
Abstract This article advocates the awareness that art exists also beyond the context. No doubt that art exists within a context. Still, it goes beyond the context. First, each artistic corpus is a structure in itself. Second, it cannot be solely considered from the point of view of context. So, a double dialogue is needed: between social science and art study, and between social science and art itself. We need a dialogue in the Bakhtinian sense, recognizing the plurality of voices, and refusing any authoritative or absolute stance of one of them. If we want to seize the singularity and textuality of the work of art, in all its aspects and consequences, we must allow for this singularity and textuality to penetrate and feed our sociological theory and research, not only as subjects but also as factors of knowledge and interpretation.